If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(0.4 + 0.5g) = 4g (0.4 * 10 + 0.5g * 10) = 4g (4 + 5g) = 4g Solving 4 + 5g = 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 4 + 5g + -4g = 4g + -4g Combine like terms: 5g + -4g = 1g 4 + 1g = 4g + -4g Combine like terms: 4g + -4g = 0 4 + 1g = 0 Add '-4' to each side of the equation. 4 + -4 + 1g = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1g = 0 + -4 1g = 0 + -4 Combine like terms: 0 + -4 = -4 1g = -4 Divide each side by '1'. g = -4 Simplifying g = -4
| 0.02x+0.01(70)=0.02(70) | | x-99=62-6x | | -4(2y+6)=16 | | -1.4(5-x)+2.5(2+x)=-3.6+x | | -2u+14+3=8u+27 | | 3a+3=3 | | 7y+5+3y+4+14y-15=180 | | 3x-86=49-6x | | 7n-8=-16+3n | | 5x(x+7)=20 | | -3(x-2)+4(2x+5)=10x-(5x-23) | | x+7+z=-11 | | -20-7x=16+9x | | 90x=585 | | 36-14x=8 | | 5x=4+-4+5x | | 20(5)=20q+5 | | 8n-2=19+5n | | 6t-12-(3t-3)=-19 | | 2(x-1)+3(x+2)=5x+4 | | 2(2x)+47=2(2x)+47 | | -40+3x=10+2x | | 6x-12=5x+17 | | 6(y-24)-6y=0 | | -40+3x=2x | | 4*x-17=23 | | 4x+x^2=179 | | 6-x=10-2x | | 4y+4x=12 | | 2x+x+2(2)+75=180 | | 20=16(16)+b*b | | 11x-66=7x+34 |